The European Experience - Rosińska, Zofia (Eidos. A Journal for Philosophy of Culture, 2025)
The essay is an introductory reflection on the process of shaping Europe, including Eastern Europe. Two sources, Athens and Jerusalem, are emphasized as an important element of the historical shaping of Europe. The author focuses on the role of the Athenian tradition in this process; and argues that at the roots of European culture lie reflexiveness and empathy as well as an ability of self-questioning. All these features can be found already in the Ancient Greek thought.